System Dynamics of School Classroom Dynamism: A Complexity Understanding - Chongbang, Karna Bahadur (Scholars’ Journal, 2021)
Classroom is a formal systemic unit integrating with conscious teacher and student activities. The rational of this paper was to present the complexity understanding as an alternative to linear systemic view to classroom context. The objective of this paper was to explore the nature of classroom dynamism under the complex system dynamics. Methodologically, it is based on the comprehensive literature review. It has discussed the influential dynamics which make classroom human subjects act, interact, and change their behaviour. It has explored the micro to macro systems that influence the didactic interaction system of teacher and student. It has analysed the interplay of the proximal and distal systemic dynamics which are to be regarded as inherent forces from complexity paradigm of a study. The core idea flowing in the paper is making meaning of the dynamism and dynamics of classroom interaction that obviously occurs in complex systemic context. It implies to accommodate complexity responding classroom research methodologies and pedagogical approaches that are expected to function in a compatible manner.